Effects of Acute and Chronic Exercises on Executive Function in Children and Adolescents: A Systemic Review and Meta-Analysis - Liu, Shijie; Yu, Qian; Li, Zaimin; Cunha, Paolo Marcello; Zhang, Yanjie; Kong, Zhaowei; Lin, Wang; Chen, Sitong; Cai, Yujun (Frontiers in Psychology, 2020)
Background: Physical exercises can affect executive function both acutely and chronically, with different mechanisms for each moment. Currently, only a few reviews have elaborated on the premise that different types of exercises have different mechanisms for improving executive function. Therefore, the primary purpose of our systematic review was to analyze the effects of acute and chronic exercises on executive function in children and adolescents. Objective: We identified acute and chronic exercise studies and randomized controlled trials (RCTs) of executive function in children and adolescents that reported overall effect, heterogeneity, and publication bias of acute and chronic exercises on executive function. Methods: We searched for RCTs of exercise interventions in children and adolescents from databases including PubMed, Web of Science, Scopus, The Cochrane Library, CNKI (China National Knowledge Infrastructure), and Wanfang, from January 1 2009 to December 31 2019. We performed methodological quality evaluations on the included literature using the Physiotherapy Evidence Database Scale (PEDro) and graded evidence with a meta-analysis using Stata 12.0 software. Results: In total, 36 RCTs were included (14 acute exercises, 22 chronic exercises); the overall results of the meta-analysis (4,577 students) indicated that acute exercises significantly improved working memory (standardized mean difference (SMD) = −0.72; 95% confidence interval (CI) −0.89 to −0.56; p < 0.001), inhibitory control (SMD = −0.25; 95% CI −0.40 to −0.09; p = 0.002), and cognitive flexibility (SMD = −0.34; 95% CI −0.55 to −0.14; p < 0.005), whereas chronic exercises significantly improved working memory (SMD = −0.54; 95% CI −0.74 to −0.33; p < 0.001), inhibitory control (SMD = −0.30; 95% CI −0.38 to −0.22; p < 0.001), and cognitive flexibility (SMD = −0.34, 95 % CI −0.48 to −0.20, p < 0.001). Conclusion: Acute and chronic exercises can effectively improve the executive function of children and adolescents. The effects on inhibitory control and cognitive flexibility are considered as small effect sizes, while the effects on working memory are considered as moderate effect size. Limited by the quantity and quality of the included studies, the above conclusions need to be verified with more high-quality studies.